Genetics in forensics - Carracedo, Angel (Henry Stewart Talks, 2009)
DNA typing in forensic analysis, DNA fingerprinting, Copy number variants, Detection of minisatellites using MLPs and SLPs, Short tandem repeats, The DNA analysis procedure in forensics, Advantages of mtDNA analysis over nucDNA, Applications of mtDNA analysis, Selecting SNPs, Forensic validation in critical samples, SNP typing applications, Casework application, DNA databases, Statistics, interpretation and communication